MENINGKATKAN HASIL BELAJAR SISWA TENTANG NILAI TEMPAT MELALUI METODE DEMONSTRASI - Mukayah Mukayah (MEDIA DIDAKTIKA, 2023)
This classroom action research aims to determine the increase in interest and Mathematics learning outcomes for students about the value of a primary school class IIA Brondong 4 First Half Year 2014/2015 through the use of demonstration. The subject of this action research is class IIA SD Negeri Brondong totaling 38 students consisting of 19 male students and 19 female students. Research procedure used is procedure classroom action research conducted in two cycles, coupled with the implementation of the activities prasiklus before the cycle begins. Pre-cycle of the data it can be concluded that there are 38 students 28 students or 83.69% are not yet complete, and only 10 students or 26.31% declared complete in learning. From that data needs to be improved so that learning by using demonstration method. Data from the first cycle can be concluded that there are 16 students or 42.11% are not yet complete, and 22 students or 57.89% declared complete in learning, while the average value of students in this cycle has reached 66.32. Of course this is not in accordance with what is expected so the need to proceed with the second cycle. In the second cycle can be concluded that there are 35 students 92.11% and only 4 students or 10.53% are not yet complete, the average has been experiencing a significant increase in line with expectations and that is equal to 89.47.